A critical analysis of the representation of Japanese culture in Japanese language textbooks - Šukelj, Katarina (Array, 2019)
Obtaining both linguistic and cultural competence in order to develop communicative proficiency is considered important in modern foreign language education, and various textbooks are used for that purpose in the field of Japanese language education in Croatia. Therefore, it is also important to examine the cultural content that these textbooks present to learners. To accomplish this goal, three intermediate-level Japanese language textbooks were critically analysed, with a focus on the portrayal of “Japanese culture”. The framework for the analysis was created by combining the findings of several previous studies, and was used to examine categories of topics presented under the designation of “culture”, or more specifically, “Japanese culture”, the prevailing types of culture presented, and to whom the culture is presented as belonging. The issue of whether or not certain ideologies relating to Japanese culture are reflected in the content of the textbooks was also investigated.